High Speed Two (HS2) : infrastructure design and construction. (ICE Publishing, 2023)
The main construction of HS2, Britain's new zero carbon, high-speed railway, began in September 2020, when delivery activity on Phase One moved from enabling works, scheme design and preparatory work to full construction of the railway. The new railway will link London and the West Midlands and eventually extend services to the North and Scotland. High-speed trains powered by zero carbon electricity will reach speeds of 225mph and transform journey times, while opening up capacity on the existing, conventional railway network. This volume of High Speed Two: Infrastructure Design and Construction from the HS2 Project, contains a collection of papers submitted to HS2 Ltd's Technical Papers Competition.